THE GENESIS OF SCIENTIFIC CONCEPTS OF CIVIL PROCESSING RELATIONS AS AN INSTITUTE OF CIVIL PROCEDURAL LAW - DENISENKO, A. (Київський національний університет імені Тараса Шевченка, 2018)
In the article the specifics of civil procedural relations as an institution of civil procedural law are analyzed. The periodization of such genes is distinguished. Characterized the features of each of these stages and their content is determined.

У статті проаналізовано специфіку цивільних процесуальних відносин як інституту цивільного процесуального права. Виокремлено періодизацію такої ґенези. Охарактеризовано особливості кожного з таких етапів і визначено їх зміст.
ҐЕНЕЗА НАУКОВИХ КОНЦЕПЦІЙ ЦИВІЛЬНИХ ПРОЦЕСУАЛЬНИХ ВІДНОСИН ЯК ІНСТИТУТУ ЦИВІЛЬНОГО ПРОЦЕСУАЛЬНОГО ПРАВА
Keywords: control organization; public control; public administration; administrative legislation; administrative and legal regulation.; організація контролю; громадський контроль; державне управління; адміністративне законодавство; адміністративно-правове регулювання.